Feasibility of Induction Docetaxel, Cisplatin, 5-Fluorouracil, Cetuximab (TPF-C) Followed by Concurrent Cetuximab Radiotherapy for Locally Advanced Head and Neck Squamous Cell Carcinoma - Charalambakis, Nikolaos; Kouloulias, Vassilis; Vaja, Helena; Pectasides, Dimitrios; Rampias, Theodoros; Economopoulos, Theofanis; Katsaounis, Panagiotis; Siolos, Spiros; Bartzi, Valentina; Perisanidis, Christos; Laschos, Konstantinos; Maragoudakis, Pavlos; et al. (Frontiers in Oncology, 2013)
Purpose: To report our experience with a sequential regimen of induction TPF-C followed by radioimmunotherapy with cetuximab in patients with locally advanced head and neck squamous cell carcinoma (HNSCC). Patients and Methods: Toxicity and outcome was retrospectively analyzed in 22 patients receiving sequential therapy with induction TPF-C followed by radioimmunotherapy between October 2008 and December 2011. Outcome was estimated using Kaplan-Meier analyses. In addition, we performed mutation analysis for PIK3CA genes and high-risk HPV-DNA detection using PCR. Results: Median follow-up was 16 months. Six patients were TNM Stage III, 15 patients IV (IVA or IVB) and 1 patient Stage II with bulky disease. During TPF-C, Grade 3 and 4 toxicities occurred in 8 patients (36.4%), dose modifications in 7 (31.8%), delays in 1 (4.5%), and unplanned admissions in 5 (22.7%). Clinical tumor response was documented in 18 of the 21 patients who completed at least 3 cycles of TPF-C (85.7%) with 3 patients developing complete response and 15 partial responses. Grade 3/4 mucositis was observed in 6 (31.6%) patients. At a median follow up of 19 months, 13 patients were alive and 9 (40.9%) had died including 7 patients as a result of disease persistence or recurrence and two as a result of unrelated causes. PIK3CA mutations were not identified and our 2 oropharynx cases were HPV negative. Conclusions: The combination of induction TPF-C with concurrent cetuximab radioimmunotherapy in patients with locally advanced HNSCC is tolerable, with encouraging efficacy. Keywords: HNSCC, TPF-C, cetuximab radiotherapy, toxicity and outcome, mutation analysis, PIK3CA, HPV-DNA.